Native shrubs and their importance for arthropod diversity in the southern Monte, Patagonia, Argentina - Martínez, Fernando Joaquín (2021)
The Monte, one of the main arid regions in Argentina, is affected by degradation processes that impact the biological communities. Arthropods are the most diverse component of the Monte fauna and play important roles in several ecosystem processes. The study of interactions between native plants and arthropods, two key elements of the Monte biodiversity, contributes to our understanding of how this ecosystem functions. Our objective was to compare the plant-dwelling arthropod assemblages associated with representative shrub species of the southern Monte and to analyse the relationship between plant architecture and the assemblage structure. We sampled arthropods using the beating method on three evergreen shrub species (Chuquiraga avellanedae, Schinus johnstonii and Larrea divaricata) at six sites during two consecutive spring seasons. We recorded shrub height, canopy area, volume and an index of canopy openness. Our results showed that native shrub species host different arthropod assemblages, partially explained by both the shrub species identity and shrub architecture (mainly canopy openness). The arthropod assemblage that lives in S. johnstonii showed the highest diversity, probably related to the plant’s intermediate canopy openness, which may determine favourable microhabitats that provide protection against adverse climatic conditions and predators. The assemblage in C. avellanedae had the lowest diversity. The closed canopy of C. avellanedae could be beneficial for a few very abundant taxa that dominate the assemblage associated with it. Implications for Insect Conservation: Our results show that these native shrubs support a wide range of arthropod taxa and guilds, contributing to maintaining the biodiversity in the southern Monte.